Armed ConAicts in Africa and War of Attrition (Global Journal of Human-Social Science, 2013)
This article analyses as a specific war of attrition, the armed conflict between a dictatorial power and the civilian population during the sharing of national wealth resulting from the exploitation of natural resources. There is asymmetry of information on the minimum share of wealth expected by every party. Unlike the traditional approach of war of attrition that requires a player who leaves first, the competition gains nothing, my approach assumes that: The civilian population earns at least its minimum share of wealth expected, regardless of the period where it leaves the competition.
Keywords: war of attrition; armed conflicts; natural resources; sharing